The Effect of Profitability and Audit Opinion on Audit Delay in Construction Sector Companies Listed on The Indonesia Stock Exchange - Rifa Ranti Nuraini; Nur Zeina Maya Sari; Uswatun Hasanah (Business Management, 2026)
This study aims to examine the effect of profitability and audit opinion on audit delay in construction sector companies listed on the Indonesia Stock Exchange. Audit delay is measured by the number of days between the company’s fiscal year-end and the date of the independent auditor’s report. Profitability is measured using Return on Assets (ROA), while audit opinion is measured using a numerical code, where companies receiving an unqualified opinion are assigned a value of 1 and companies receiving opinions other than unqualified are assigned a value of 0. This study uses a quantitative approach with descriptive and verification methods. The data used are secondary data obtained from annual financial reports and independent auditor reports of construction sector companies listed on the Indonesia Stock Exchange during the 2019–2024 period. The sampling technique used is purposive sampling, resulting in 83 observations. The data were analyzed using multiple linear regression with SPSS. The results show that profitability has no significant effect on audit delay, while audit opinion has a negative and significant effect on audit delay. The results show that profitability has no significant effect on audit delay, while audit opinion has a negative and significant effect on audit delay. The F-test result shows that profitability and audit opinion have a significant effect on audit delay. The adjusted R Square value of 0.097 indicates that profitability and audit opinion explain 9.7% of the variation in audit delay, while the remaining 90.3% is explained by other factors outside the model. The descriptive results also show that profitability is relatively low, audit opinion is generally good, and the average audit delay is approximately 86 days.